A HIDDEN COST OF INDONESIA SINGLE RISK MANAGEMENT: SCRUTINY VIS A VIS SERVICES - Ika Riswanti Putranti (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Trade facilitation services faces two major challenges which serves as a scrutiny and service. Erosion of scrutiny functions will pose a threat to national security, for instance food safety, goods forgery, fraud, and other form of transnational crimes. While the erosion of service function will impede the flow of goods which lead to economic injury. This paper will analyze to what extent Indonesia Single Risk Management is able to reduce the hidden cost in scrutiny vis a vis service. This is a normative study and employing statute approach, conceptual approach, and comparative approach. The data analysis used descriptive qualitative method. This study finds that harmonization of the determination of risk values and risk indicators in each Ministry/Agency can be used to minimize or manage hidden cost within trade facilitation. Keywords: trade facilitation, risk management, service, scrutiny, hidden cost, customs.